Analysis of the Influence of General Allocation Funds (DAU), Special Allocation Funds (DAK) and Regional Original Income (PAD) on Economic Growth in South Buru Regency - Fatimah Salampessy; Djufri Rays Pattilouw; Yerimias Manuhutu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to determine the influence of the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Regional Original Income (PAD) on economic growth. The data used are secondary data sourced from competent government institutions. The data are then analyzed using statistical tools in the form of multiple linear regression. The research results show that DAK and PAD have a negative, though insignificant, effect on economic growth, while DAU has a positive and significant effect. This could indicate that the economy of South Buru Regency still has a significant fiscal dependence on the central government.